Konsep Suami sebagai Pemimpin dalam Pernikahan Al-Quran Surah an-Nisa’ ayat 34 - Rosita, Naela; Fatimah Azzahra; Amiratunil Khaira (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The difference in interpretation of the meaning of qawwam in the Qur'an, Surah An-Nisa' 34, has given rise to many conflicts in the concept of the relationship between men and women in the household. Where according to some figures, qawwam is considered a full right for men as leaders in the household and vice versa, qawwam is considered a conditional right of cause and effect that must be fulfilled in a marriage relationship. The purpose of this study is to find out multidisciplinary according to the views of prominent scholars, scholars of interpretation, hadith and feminists about the meaning of qawwam in the Qur'an, Surah An-Nisa 34. The type of research used in this study is descriptive qualitative with a data collection method based on library research. In this study, it was found that in essence the concept of a husband as a leader/qawwam in marriage is fully related to the fulfillment of a husband's rights and obligations in marriage in accordance with the qodrat determined by Allah.